2018
DOI: 10.1519/jsc.0000000000002293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2% Dehydration on Lactate Concentration During Constant-Load Cycling

Abstract: Green, JM, Miller, B, Simpson, J, Dubroc, D, Keyes, A, Neal, K, Gann, J, and Andre, T. Effects of 2% dehydration on lactate concentration during constant-load cycling. J Strength Cond Res 32(7): 2066-2071, 2018-The lactate [La] threshold (LT) can predict endurance performance potential. Dehydration may alter LT. This study examined effects of dehydration on [La] response during constant-load cycling. Recreationally fit (V[Combining Dot Above]O2peak = 48.7 ± 5.2 ml·kg·min) male participants (n = 9) completed 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Another study(10) reveled that lactate level was not significantly associated with length of hospital stay (p = 0.115) or the length of time to diabetic ketoacidosis resolution (p = 0.143).In the current study, there was a no significant difference between the serum lactate levels and different hydration states of the patients (p = 0.4). In disagreement with our study, another study(13) showed a strong relation between systematic changes in lactic acid and associated physiological responses resulting from previous day dehydration.…”
contrasting
confidence: 99%
“…Another study(10) reveled that lactate level was not significantly associated with length of hospital stay (p = 0.115) or the length of time to diabetic ketoacidosis resolution (p = 0.143).In the current study, there was a no significant difference between the serum lactate levels and different hydration states of the patients (p = 0.4). In disagreement with our study, another study(13) showed a strong relation between systematic changes in lactic acid and associated physiological responses resulting from previous day dehydration.…”
contrasting
confidence: 99%
“…Moquin and Mazzeo [19] observed a 12% decrease in power at lactate threshold after ~2.6% body mass loss via fluid restriction compared with a euhydrated state. Similarly, Green et al [24] observed that 2% dehydration increased HR and blood lactate during steady-state cycling compared to cycling in a euhydrated state. Kenefick et al [25] found that the lactate threshold occurred at a lower exercise intensity after 4% exercise-induced hypohydration.…”
Section: Discussionmentioning
confidence: 91%
“…We found an earlier onset of lactate accumulation with increasing weight loss through fluid abstinence. Previous investigations in other athlete populations have found higher blood lactate at submaximal intensities with weight-reducing dehydration practices [ 40 , 41 ]. Nine recreationally fit males demonstrated elevated blood lactate at all time points during a constant-load cycle-ergometer task following a 2%BMC via a warm water bath the previous evening [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations in other athlete populations have found higher blood lactate at submaximal intensities with weight-reducing dehydration practices [ 40 , 41 ]. Nine recreationally fit males demonstrated elevated blood lactate at all time points during a constant-load cycle-ergometer task following a 2%BMC via a warm water bath the previous evening [ 40 ]. Similarly, a study of intercollegiate wrestlers has demonstrated a lower treadmill velocity required to achieve the lactate threshold following exercise in a rubberized sweat suit [ 41 ].…”
Section: Discussionmentioning
confidence: 99%